Urinary Morphine Detection by Gas Chromatography–Mass Spectrometry for Assessing Methadone Treatment Adherence - Wimpy Wimpy; Tantri Daniawaty (PT.Mantaya Idea Batara, 2026)
Background: Opioid use disorder is a significant public health issue, and adherence to Methadone Maintenance Therapy (MMT) is critical for successful treatment. Self-reported adherence can be biased, so objective laboratory measures are valuable. Urinary morphine detection by Gas Chromatography–Mass Spectrometry (GC-MS) indicates recent illicit opioid use and may signal lower methadone adherence. This study examined the association between GC-MS-confirmed urinary morphine detection and methadone adherence in MMT patients. Methods: This cross-sectional analytical study included 20 MMT patients at the PTRM Clinic of Gambir Public Health Center, selected by quota sampling. Urinary morphine was measured using GC-MS. Treatment adherence was assessed with a modified Morisky Medication Adherence Scale-8 (MMAS-8) and medical records. Data were analyzed using the Fisher–Freeman–Halton Exact Test, with Cramer’s V describing the strength of association. Result: Urinary morphine was detected in 2 participants (10%), while 18 (90%) had results below the detection limit. High, moderate, and low adherence were observed in 65%, 30%, and 5% of participants, respectively. The Fisher–Freeman–Halton Exact Test showed a statistically significant association between urinary morphine detection and methadone adherence categories (p = 0.032). Although Cramer’s V was 0.733, this result should be interpreted with caution due to the small number of positive cases. Conclusion: GC-MS-confirmed urinary morphine detection was significantly associated with lower methadone adherence and may complement behavioral and clinical assessments by providing objective evidence of recent illicit opioid use. These findings are preliminary, and larger multicenter longitudinal studies are needed to confirm their clinical relevance.